Presence, abundance and bacterivory of the mixotrophic algae Pseudopedinella (Dictyochophyceae) in freshwater environments - Gerea, Marina (2016)
The genus Pseudopedinella has been described as mixotrophic; however, ecological information about this algal stramenopile (Heterokonta) is unclear. We investigate the environmental conditions that determine the presence, abundance and bacterivory rates of this genus in freshwater systems. To this end we analyzed 54 water bodies with different limnological features distributed along a latitudinal and trophic gradient in northern Patagonia (Argentina) and the Antarctic Peninsula. In addition, 14 grazing experiments were carried out in order to estimate ingestion rates and impact on the bacterioplankton. Our results indicate that this genus is exclusively found in oligotrophic environments, and that it develops well in a wide range of temperatures. Average cell-specific grazing rate was 2.83 bacteria cell-1 h-1, with a maximum value of 6.74 bacteria ml-1 h-1. Interestingly, grazing increased with prey abundance and decreased with increasing nutrient availability. These patterns are common in highly bacterivorous protists that use phagotrophy as a main source of nutrient acquisition. Despite their usually low abundance (avg. 182 cells ml-1), this single genus was responsible for up to 24% (avg. 10%) of the total grazing impact exerted by all phagotrophs in these lakes. Overall, our results support the idea that Pseudopedinella is a highly bacterivorous group of freshwater protists, with the ability to develop well in oligotrophic conditions and with a potentially significant impact on bacterioplankton.